Analisis Kedudukan Saksi sebagai Syarat Sah dalam Pernikahan - Ardiansyah Ardiansyah; Anisah Syakirah; Muhammad Abdillah Hasby (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research analyzes the role of witnesses in marriage contracts, especially differences of opinion among ulama. The majority of ulama are of the opinion that the presence of witnesses is a legal requirement in a marriage contract because of its function as proof, preventing disputes, and safeguarding the benefit of the people. However, Abu Tsaur has a different view, namely that the marriage contract remains valid without the presence of witnesses. This research examines the arguments that support these two opinions and analyzes the causes of differences of opinion, which are influenced by historical, cultural factors and the ijtihad of the ulama. Through normative and comparative methods, this research concludes that these differences of opinion show the dynamics of ijtihad in Islam and the importance of understanding the historical context and objectives of the Shari'a in understanding a law. In the context of Indonesian positive law, the presence of witnesses is also regulated in the marriage law, but with a different emphasis. This research has practical implications for the implementation of marriage contracts, resolving marriage disputes, and the development of family law in Indonesia.